Columnar Organization of the neurons in theventral horn of the cervical and upper thoracic spinal cord in Albino Rat - Saeed, Muhammad; Janjua, Muhammad Zahoor (Journal of Postgraduate Medical Institute, 2011)
The columnar organization of the motoneurons in the ventral horn of the cervical and upper thoracic spinal thoracic spinal cord in adult albino rat was studie by Elliott's method. The motoneurons were not homogenously distributed throughout the ventral grey, but instead formed relatively well defined groups if seen in cross sections or nearly continous columns if seen in logitudinal sections. Some of these columns extended throught theentire length of the cervical and upper thoracic spinal cord; others were present only in the cervical enlargement. Between 5th cervical and 1st thoracic segments more cell columns were noticed than those in the rostral and caudal segments. This increase in columns occurred in the ventrolateral and dorsolateral groups which formed several sub-groups, however some degree of fusion existed between few of the columns described.